(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: Estimate the incidence of the confounding lesions (CL) with pressure injuries in an intensive care unit of an oncology hospital, to characterize the patients and the confused injuries. Methods: Prospective cohort study conducted in an adult intensive care unit of an oncology hospital in Belo Horizonte, Minas Gerais. The sample consisted of 67 patients who met the inclusion criteria. The data were collected during the period of one month by single researcher stomatherapist and registered in the form prepared for this purpose. The study was approved by the Research Ethics Committee. Results: 58.1% were women, 65.1% were elderly, 51.2% were white, with gastrointestinal cancer predominating, 71.6% were using adjuvant chemotherapy, with below-normal body mass index, 100% had urinary incontinence or fecal and diaper use. The incidence of these injuries was 35.8%, and the average time for their onset was 11 days after admission. Most patients had skin changes such as maceration, peeling, erythema, dehydration, and edema. Conclusion: We can conclude that the incidence of confused injuries is high in oncology patients admitted to intensive care units. It was possible to describe the demographic and clinical profile of the patients of the sample and to characterize the injuries and the skin around them.